Elements of Petroleum Geology - Selley, Richard C.; Sonnenberg, Stephen A. (London: Academic Press, 2023)
Elements of Petroleum Geology, Fourth Edition is a useful primer for geophysicists, geologists and petroleum engineers in the oil industry who wish to expand their knowledge beyond their specialized area. It is also an excellent introductory text for a university course in petroleum geoscience. This updated edition includes new case studies on non-conventional exploration, including tight oil and shale gas exploration, as well as coverage of the impacts on petroleum geology on the environment. Sections on shale reservoirs, flow units and containers, IOR and EOR, giant petroleum provinces, halo reservoirs, and resource estimation methods are also expanded.
Includes Subject Index
Keywords: Petroleum$1 (BGeologys; Petroleum$1 (BProspectings; Sedimentary basins; Structural geology